Principal Managerial System in Creating Quality Culture in SMP Muhammadiyah 3 Waru - Anik Isticharoh; Yayuk Fauziah; Taufiq Churrohman (International Consortium of Education and Culture Research Studies, 2020)
Muhammadiyah 3 Waru Junior Highschool is an Islamic school, which established since 1975. The learning activities at Muhammadiyah 3 Waru Junior Highschool are organized by the school curriculum in collaboration with the national curriculum, Muhammadiyah, Tahfidz, and International, EPP curriculum. The management system in the field of education is a process created to coordinate various educational resources, facilities and infrastructure needed with a view to achieving educational goals and objectives. This study aims to examine more further about the principal's managerial system in creating a quality culture in Muhammadiyah 3 Waru Junior Highschool by describing the problems faced by the principal such as: 1) the form of the principal's management concept, 2) the steps taken by the principal in realizing the concept of management in schools, 3) the form of the concept of quality schools that are built, 4) the efforts of the school in creating a quality culture, 5) the role of the principal in creating a quality culture. This research is a qualitative research field by using descriptive methods that aim to make sensing (description) systematically factual and accurate about the facts and characteristics of the population or a particular area. The approach used is a phenomenological approach that seeks to understand the meaning of events and their links to ordinary people in certain situations, in this research emphasizes the subjective aspects of the people studied. This study produced 5 answers to the problems that fit the focus of the study presented as follows: The concept of the principal management of the Muhammadiyah 3 Waru Junior Highschool uses an Islamic leadership management system, prioritizing the resources of its school residents.